Successful Retention of Postpartum Genital Prolapse with Buhner’s Suture in Three Jaffarabadi Buffaloes – A Case Study - Parmar, Kirankumar; Vadher, Dhruv; Solanki, Jayesh; Patel, Meet; Devmurari, Yash; Pranami , Ruchir (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The eversion of genital organs or their prolapse is a condition mostly seen during or within a few hours after postpartum in cows and buffaloes. Genital prolapse is the dislodgment of intra-pelvic structures like the vagina, uterus, and bladder from the normal anatomical position through the vaginal opening. It is regarded as an emergency condition and should be managed before excessive edema, mucosal trauma, contamination, and fatal haemorrhage lead to a grave prognosis (Miesner and Anderson, 2008). This communication reports successful management of uterine prolapse in three Jaffarabadi buffaloes using Buhner᾽s suture as a retention technique.